2021
DOI: 10.1111/jcmm.16401
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells loaded with exosomes derived from cancer stem cell‐enriched spheroids as a potential immunotherapeutic option

Abstract: Cancer stem cells (CSCs) are responsible for therapeutic resistance and recurrence in colorectal cancer. Despite advances in immunotherapy, the inability to specifically eradicate CSCs has led to treatment failure. Hence, identification of appropriate antigen sources is a major challenge in designing dendritic cell (DC)‐based therapeutic strategies against CSCs. Here, in an in vitro model using the HT‐29 colon cancer cell line, we explored the efficacy of DCs loaded with exosomes derived from CSC‐enriched colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…The HT-29 cancer cells were cultured in DMEM/High glucose medium (Gibco, Germany) supplemented with 10% fetal bovine serum (Gibco, Germany), 1% non‐essential amino acids (Gibco, Germany), 2 mM l -glutamine (Gibco, Germany) and 1% Penicillin–Streptomycin (Biowest, France) at 37 °C in 5% CO 2 and 95% humidified incubator. Colorectal CSC-enriched spheroids were generated using hanging droplet technique of HT-29 cancer cells descripted earlier [ 63 ]. Spheroid culture medium included DMEM/F12 (Gibco, Germany), supplemented with 2% B27 (Gibco, Germany), 10 ng/ml of basic fibroblast growth factor (bFGF), 20 ng/ml epidermal growth factor (EGF) (PeproTech, USA), 1% nonessential amino acids, 2 mM l -glutamine, and 1% Penicillin–Streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…The HT-29 cancer cells were cultured in DMEM/High glucose medium (Gibco, Germany) supplemented with 10% fetal bovine serum (Gibco, Germany), 1% non‐essential amino acids (Gibco, Germany), 2 mM l -glutamine (Gibco, Germany) and 1% Penicillin–Streptomycin (Biowest, France) at 37 °C in 5% CO 2 and 95% humidified incubator. Colorectal CSC-enriched spheroids were generated using hanging droplet technique of HT-29 cancer cells descripted earlier [ 63 ]. Spheroid culture medium included DMEM/F12 (Gibco, Germany), supplemented with 2% B27 (Gibco, Germany), 10 ng/ml of basic fibroblast growth factor (bFGF), 20 ng/ml epidermal growth factor (EGF) (PeproTech, USA), 1% nonessential amino acids, 2 mM l -glutamine, and 1% Penicillin–Streptomycin.…”
Section: Methodsmentioning
confidence: 99%
“…8 Therefore, simultaneously targeting existing CSCs and de novo generation of CSCs is pivotal to eliminate tumors. [20][21][22] Previous studies have shown that CSC-derived exosomes play a role in the acquired resistance of tumor cells to chemotherapeutic agents. 13 In this study, we found that exosomes derived from LCSCs increase the stemness of differentiated cancer cells by upregulating expression of NANOG, enhancing resistance to regorafenib.…”
Section: Discussionmentioning
confidence: 99%
“…The DCs-based vaccines have been developed as a promising and effective strategy to facilitate CSC eradication, and in two examples, DCs loaded with CSCs-lysate [ 72 ] or CSCs-derived exosomes [ 73 ] have shown promising preclinical immunotherapeutic outcomes. However, defects in MHC-I and the presence of tolerogenic T cells recognizing TAAs result in the low immunogenicity of these antigens.…”
Section: Immunotherapies Targeting Cscsmentioning
confidence: 99%